Strategi Balai Sentra Bahagia Kemensos dalam Mendukung Kemandirian Penerima Manfaat - Erga Dwo Winatra (JURNAL PENDIDIKAN DAN ILMU SOSIAL (JUPENDIS), 2025)
Balai Sentra Bahagia, under the Ministry of Social Affairs of the Republic of Indonesia, serves as a pivotal institution in Medan, North Sumatra, dedicated to the social rehabilitation and empowerment of vulnerable populations, including persons with disabilities, the elderly, and individuals facing social challenges. The center implements comprehensive strategies aimed at fostering self-reliance among its beneficiaries. These strategies encompass initial assessments to identify individual needs, followed by tailored vocational training programs in areas such as sewing, carpentry, culinary arts, and hydroponic farming. Additionally, the center provides psychosocial support, character development sessions, and facilitates access to entrepreneurship opportunities and market networks. Notably, initiatives like the Sentra Kreasi ATENSI (ATENSI Creative Center) have been instrumental in promoting beneficiary products through bazaars and exhibitions, enhancing their economic independence. This paper explores the effectiveness of these empowerment strategies in promoting self-sufficiency among beneficiaries, offering insights into best practices for social rehabilitation.